Budd chiari syndrome: A case report on a rare disorder (Indian Journal of Case Reports, 2021)
Budd Chiari syndrome (BCS) is a rare disease that threatens life due to a hepatic vein blood flow obstruction. As per the literature, thrombosis is a significant factor for hepatic venous obstruction. It can treat BCS based on the severity of the patient’s condition by three methods like hepatic vein angioplasty, interventional radiology stenting with direct intrahepatic portosystemic shunt, or liver transplantation. We describe the case of a 34-years-old female patient who presented with abdominal distension and generalized weakness with a history of BCS. A cooperative collaboration of hepatologists and interventional radiologists helps in effectively treating the syndrome.